Foraging guild perturbations and ecological homogenization driven by a despotic native bird species. (April 2014) - Howes, Alison; Mac Nally, Ralph; Loyn, Richard; Kath, Jarrod; Bowen, Michiala; McAlpine, Clive; Maron, Martine; Lens, Luc
<x xml:space="preserve">Abstract</x> Anthropogenic activities often cause specialized and fragmentation‐sensitive species to be replaced by competitive commensal or invasive species, resulting in reduced diversity and biotic homogenization. However, biotic homogenization driven by increased dominance of a native species has rarely been investigated. Increased abundance of competitive species can have important consequences for assemblage dynamics including homogenization of foraging strategies and, potentially, ecological services. This study assesses how changes to bird assemblages due to the occurrence of an aggressive honeyeater alter the foraging profiles of avifauna in 400 woodland sites in nine study regions across eastern Australia, and explores the potential implications for ecological services. We compared beta diversity among sites with a high and low abundance of the aggressive Noisy Miner Manorina melanocephala. Shifts in ecological characteristics of bird assemblages of sites with high and low abundance of Noisy Miners, including mean and variation in niche position, bill length and body size, were explored. Sites with a high abundance of Noisy Miners were more taxonomically and ecologically homogeneous and had fewer species than sites with a low abundance of Noisy Miners. The mean niche positions of bird assemblages changed and were increasingly dominated by larger vertebrate feeders, granivores and frugivores as Noisy Miner abundance increased. The mean body size and bill length of the insectivore species present at a site increased with Noisy Miner abundance. This change in the bird community along with reduced diversity in foraging strategies implies a loss of the ecological functions provided by smaller‐bodied species, potentially affecting plant dispersal and regeneration, insect herbivory and ultimately woodland resilience. Our study demonstrates a substantial shift in ecological profile over a broad geographical area as a result of a single native species.